Positive relationships of character strengths with fitness and physical activity in primary school children - Kensaku Sasayama; Tomoya Imura; Minoru Adachi; Tazuko Aoki; Minglu Li (Health Psychology and Behavioral Medicine, 2023)
ABSTRACTObjective This study is the first to examine the relationship between character strengths, objective physical fitness, and physical activity in primary school children.Design This cross-sectional study was conducted in 2016 and 2017 at a school in Japan. Main Outcome Measures: We obtained informed consent from 236 fourth-grade students; 122 fifth-grade students; and 142 sixth-grade students. After excluding participants with missing data, 473 children (247 boys and 226 girls; aged 9–12 years) with informed consent were included in the study. We measured character strengths, physical fitness, and/or physical activity of fourth- to sixth-grade participants.Results Among boys, the total score of physical fitness was significantly associated with perseverance-honesty, courage-ideas, compassion-gratitude, and fairness-care (p < 0.05). Among girls, the total score of physical fitness was significantly associated with perseverance-honesty, courage-ideas, and compassion-gratitude (p < 0.05). Regarding the relationship between character strengths and physical activity, perseverance-honesty was significantly associated with total steps and moderate-to-vigorous physical activity (MVPA), whereas courage ideas were significantly associated with total steps (p < 0.05) in boys. In girls, perseverance-honesty was associated with MVPA (p < 0.05).Conclusions Our findings revealed that character strengths are positively associated with objective physical fitness and physical activity in primary-school children.